Aniseikonia and anisometropia: implications for suppression and amblyopia. (21st February 2019) - South, Jayshree; Gao, Tina; Collins, Andrew; Turuwhenua, Jason; Robertson, Kenneth; Black, Joanna
Abstract : Aniseikonia is a difference in the perceived size or shape of images between eyes, and can arise from a variety of physiological, neurological, retinal, and optical causes. Aniseikonia is associated with anisometropia, as both anisometropia itself and the optical correction for anisometropia can cause aniseikonia. Image size differences above one to three per cent can be clinically symptomatic. Common symptoms include asthenopia, headache and diplopia in vertical gaze. Size differences of three and more impair binocular visual functions such as binocular summation and stereopsis. Above five per cent of aniseikonia, binocular inhibition or suppression tend to occur to prevent diplopia and confusion. Aniseikonia can be measured using a range of techniques and can be corrected or reduced by prescribing contact lenses or specially designed spectacle lenses. Subjective testing of aniseikonia is the only way to accurately measure the overall perceived amount of aniseikonia. However, currently it is not routinely assessed in most clinical settings. At least two‐thirds of patients with amblyopia have anisometropia, thus we may expect aniseikonia to be common in patients with anisometropic amblyopia. However, aniseikonia may not be experienced by the patient under normal binocular viewing conditions if the image from the amblyopic eye is of poor quality or is too strongly suppressed for image size differences to be recognised. This lack of binocular simultaneous perception in amblyopia may also prevent the measurement of aniseikonia, as most common techniques require direct comparisons of images seen by each eye. Current guidelines for the treatment of amblyopia advocate full correction of anisometropia to equalise image clarity, but do not address aniseikonia. Significant image size differences between eyes may lead to suppression and abnormal binocular adaptations. It is possible that correcting anisometropia and aniseikonia simultaneously, particularly at the initial diagnosis of anisometropia, would reduce the need to develop suppression and improve treatment outcomes for anisometropic amblyopia.